Examining Government Support for Disability Sports Development - Kasiyanto, Teguh (Indonesian Journal of Disability Studies, 2023)
Even though there have been many scientific articles that discuss people with disabilities in Indonesia, studies on government support for the development of special sports for people with disabilities are still few. I will provide an overview of government support for people with disabilities in Indonesia in general and then focus on government support for the development of disability-specific sports. The method in the preparation of this article is a qualitative research method with a thematic study approach with the main subject of literature on policies on documents containing disability in Indonesia. To focus the study of the document, I take Jember Regency as the smallest scope of the source of the document. After that, I looked for articles that regulate sports for people with disabilities. This article will divide the discussion into several sub-themes according to the support provided by the government and the support that still needs to be optimized. Government support is meant to support the development of sports, accessible facilities and infrastructure as well as funding support. This article seeks to provide input on the development of special sports for persons with disabilities in Indonesia.